A P.M. está em greve: representações sociais na mídia jornalística - Rocha, Joelson de Maria (2021)
In 2017, a class of workers that represents part of the public security structure of the state of Espírito Santo, the Military Police, went on strike. This event, which had a major impact in the daily life of capixabas, was widely reported by the state’s media, specially on the press. Among all the journalistic work, the 23 days of coverage by one of the main newspapers in the region, A Gazeta, stands out. It addresses the first movements by police officer’s relatives, the evolution of the strike, its social, economic, and political impacts, and the measures adopted by Executive, Legislative, and Judiciary powers in face of the security crisis. From this coverage, social representations of important actors emerge. The objective of this research is to analyze, from the perspective of Critical Discourse Analysis, how the newspaper A Gazeta represents police officers, policemen “wives”, shopkeepers, the population and the State. In order to do, a corpus was assembled containing headlines and subheadlines of the news and reports that composed this coverage. To carry out this work, which intends to contribute to the comprehension of this important moment in the state’s public security, contributions from Philosophy, Sociology and Social Psychology about the phenomenon of social representation will be examined. Then, some of the socio-semantic categories proposed by van Leeuwen (1996) and Van Dijk’s (2016, 2012, 2010, 2001) categories of discourse structures will be employed in order to describe how these social actors are sociocognitively represented through the creation and activation of mental models. The results point to a social representation which builds an argumentative project aimed at defining stabilizing participants and destabilizing participants based on the strategy of discourse polarization.